2017
DOI: 10.2147/ndt.s127564
|View full text |Cite
|
Sign up to set email alerts
|

Can melatonin prevent or improve metabolic side effects during antipsychotic treatments?

Abstract: In the last two decades, second-generation antipsychotics (SGAs) were more frequently used than typical antipsychotics for treating both psychotic and nonpsychotic psychiatric disorders in both children and adolescents, because of their lower risk of adverse neurological effects, that is, extrapyramidal symptoms. Recent studies have pointed out their effect on weight gain and increased visceral adiposity as they induce metabolic syndrome. Patients receiving SGAs often need to be treated with other substances t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 81 publications
(92 reference statements)
0
14
0
2
Order By: Relevance
“…Because several clinical and social conditions that present hypomelatoninemia, such as LAN, diabetes, and neurological disorders (2), are associated with increased body fat, a reduction in BAT as a result of the hypomelatoninemic condition could be a possible explanation for this correlation (23), but we do not have any direct evidence of that. Importantly, we do not believe that melatonin could be an independent antiobesity drug, but rather, a deficiency in melatonin could lead to weight gain in the long-term (5), and its replacement or supplementation could prevent weight gain in some obesogenic situations, such as reduced BAT activity after the use of antipsychotic drugs (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because several clinical and social conditions that present hypomelatoninemia, such as LAN, diabetes, and neurological disorders (2), are associated with increased body fat, a reduction in BAT as a result of the hypomelatoninemic condition could be a possible explanation for this correlation (23), but we do not have any direct evidence of that. Importantly, we do not believe that melatonin could be an independent antiobesity drug, but rather, a deficiency in melatonin could lead to weight gain in the long-term (5), and its replacement or supplementation could prevent weight gain in some obesogenic situations, such as reduced BAT activity after the use of antipsychotic drugs (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…As far as human endocrine and metabolic diseases are concerned, the importance of regular melatonin daily secretion in determining adequate energy balance and glucose metabolism is seen in several articles that showed a negative correlation between the levels of nocturnal melatonin secretion and BMI, insulin resistance (IR), and type 2 diabetes incidence (10,11). In addition, a few articles demonstrated that chronic therapeutic daily melatonin administration can induce a reduction of fat mass and an increase of lean mass besides being able to counteract antipsychotic drug-induced metabolic adverse effects, including overweight (12)(13)(14). However, the exact mechanism by which melatonin exerts its metabolic effects in humans is not known.…”
mentioning
confidence: 99%
“…Además, se ha demostrado una relación entre la obesidad y la reducción del sueño, así como la privación del sueño en ratas se ha asociado con hiperfagia. Los efectos metabólicos de la melatonina, tanto central como periférica, directa e indirecta, se dirigen a la mayoría de los trastornos metabólicos notificados durante y después del tratamiento con antipsicóticos de segunda generación en niños, adolescentes y adultos 17 .…”
Section: Resultsunclassified
“…A link has also been demonstrated between obesity and reduced sleep, and sleep deprivation in rats has been associated with hyperphagia. The central and peripheral, direct and indirect metabolic effects of melatonin are geared towards most of the metabolic disorders reported during and after treatment with second-generation antipsychotics in children, adolescents and adults 17 .…”
Section: Resultsmentioning
confidence: 99%
“…De forma análoga, um estudo com melatonina unicamente após a menopausa mostrou uma redução de massa gorda e um aumento de massa magra, embora com pequeno efeito sobre o IMC238 . Alguns estudos observaram que a administração de melatonina reduziu de forma significante o ganho de peso e os fatores de risco cardiometabólicos, muito comuns com o uso de antipsicóticos atípicos237,239,240,242,243 .Embora a melatonina seja pouco estudada na regulação metabólica em humanos, ao contrário do que ocorre em animais, como indicado acima, ela tem diversos outros usos clínicos potenciais, muitos com dados robustos e muitos ainda em investigação143,[244][245][246][247][248][249] . A melatonina é empregada em diversos países do mundo como medicação de venda livre sem receita (OTC do inglês over-the-counter) ou como suplemento alimentar sem uma adequada regulação por parte das agências sanitárias249 .…”
unclassified